An experimental investigation of hard-to-float fine coal. Issue 14 (17th July 2016) - Cheng, G.
ABSTRACT: To improve the separation efficiency of hard-to-float fine coal, the properties of coal sample were analyzed, the roughing conditions were explored, and the three different flotation flows were compared. The optimal roughing reagent doses were collector 200 g/t, frother 90 g/t. The separation effect improved after adopting classified flotation, especially the combined process of the flotation machine and the flotation column, recovery increased by 4.15%, and ash decreased by 0.22%. Meanwhile, this process is easily applied in industrial production.